Prevalence of visual impairment among school children in Burla, Odisha: a cross-sectional study - Meher, Trupti; Hota, Gopeswari; Panda, Smita Kumari; Pradhan, Subrat Kumar (International Journal Of Community Medicine And Public Health, 2026)
Background: According to WHO, approximately 19 million children and adolescents 5-15 years of age suffer from visual impairment. Priority should be given to effective methods of vision screening in children and correction as early as possible. Methods: The study was conducted as a cross-sectional study among 340 school students in Burla, in the age group of 10–15 years. A child with a presenting maximum vision ≤6/12 Snellen equivalent in the better eye is considered visually impaired. Details of near work and outdoor activities were collected from their parents by administering a pretested questionnaire. Data was analyzed using EPI Info software version 7. Results: The overall prevalence of visual impairment (vision ≤6/12) among the study participants was 11.8% (95% confidence interval = 8.8% to 15.6%). Participants who spend more hours reading/writing and on a digital screen have a higher prevalence. Conclusions: The study highlights the high prevalence of undetected visual impairment in school children and the importance of early detection, treatment, and compliance with using corrective spectacles, which halts the further progression of low vision.